The consumer projection laws – an overview / Kahirul Anuar Abdul Rahman - Abdul Rahman, Kahirul Anuar (Faculty of Law, 1987)
Literally, consumer in a user of product in which is used domestically, and not in manufacturing. Legally, it means a person to or for whom the goods or services are, or are sought to be supplied in the course of a business carried on by the supplier and who does not receive them in a course of a business carried on by him. Consumer in other words is one who consumes or individuals who purchase, use, maintain, and dispose of products and services. Consumer in a real life is a member of board class of people who are affected by pricing policies, financing practices, quality of goods and services, credit reporting, debt collection, and other trade practices for which state and federal consumer protection laws are enacted.